1960
DOI: 10.1136/hrt.22.3.361
|View full text |Cite
|
Sign up to set email alerts
|

Immediate and Remote Effects of Resection on the Hypertension in Coarctation of the Aorta

Abstract: Twenty-five years ago Sir Thomas Lewis summarized the state of knowledge regarding this important congenital lesion (34)* and thought that "new records of cases can have little value unless they reveal new features of interest and importance to the study of the condition." Yet hardly more than a decade later the first patients with coarctation of the aorta were to be successfully operated upon in Sweden (11) and the United States (23). A new era of progress in the treatment and understanding of the pathologica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
1

Year Published

1964
1964
1981
1981

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 29 publications
0
8
1
Order By: Relevance
“…These data are presented, as has been done in the past (17)(18)(19), to give information as to the severity of the coarctation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These data are presented, as has been done in the past (17)(18)(19), to give information as to the severity of the coarctation.…”
Section: Resultsmentioning
confidence: 99%
“…The preoperative and postoperative differences between the femoral and the brachial pressure have been reported in detail previously (18,19) and are included in this paper only as an indication of the severity of the lesion and as evidence that surgical correction of the coarctation was adequate. This appears to be the case even though a significant residual difference (4 mm Hg) was noted between the upper and the lower extremities in the postoperative measurements.…”
Section: Discussionmentioning
confidence: 99%
“…The persistent elevation of blood pressure for several months following successful coarctation resection has been reported in 4 to 7 per cent of the patients in longterm follow-up studies. 'll 16,17,20,21 March et al 9 reported that blood pressure fell slowly after operation; only 33 per cent of their patients were normotensive at the time of discharge.…”
Section: Resultsmentioning
confidence: 99%
“…Even though the repair of CoA has significantly reduced BP in the majority of patients (7, 106,108,149), hypertension persists in a number of them. The reported incidence of postoperative normotension is around 80 "/o in large series (7, 96,154).…”
Section: Blood Pressure Reductionmentioning
confidence: 98%
“…Bleeding problems occur quite frequently during the operation and in the early postoperative phase. Apart from those due to surgical failures these complications are attributed to the stress changes that have developed in the aorta and collaterals and to the high aortic BP immediately after surgery (72, 106,166). Cases of the heart stopping during the operation are most often attributed to hypotension after bleeding problems (86).…”
Section: Surgical Cornphicationsmentioning
confidence: 99%